EVALUATION OF THE TOXICITY AND REVERSIBILITY PROFILE OF THE AQUEOUS SEED EXTRACT OF HUNTERIA UMBELLATA (K. SCHUM.) HALLIER F. IN RODENTS - Adeneye, A. A.; Adeyemi, O. O.; Agbaje, E. O.; Banjo, A. A. F. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Hunteria umbellata (K. Schum.) Hallier f. (family: Apocynaceae) is reputed for the folkloricmanagement of labour, pain and swellings, stomach ulcers, diabetes, obesity, and anaemia, with no scientificreport of its toxicity and reversibility profile. The present study was, therefore, aimed at investigating the in vivotoxicity and reversibility profile of the aqueous seed extract of Hunteria umbellata (HU). The acute oral andintraperitoneal toxicity studies of HU were determined in Swiss albino mice while its 90-day oral toxicity andtoxicity reversibility profile on anthropometric, biochemical, haematological and histopathological parameterswere also assessed using standard procedures. Results showed that the LD 50 values for the acute oral andintraperitoneal toxicity studies for HU were estimated to be 1000 mg/kg and 459.3 mg/kg, respectively. Visiblesigns of immediate and delayed toxicities including starry hair coat, respiratory distress, and dyskinesia wereobserved. For the chronic oral toxicity study, HU administered for 90 days produced significant (p<0.001)reductions in the weight gain pattern and significant (p<0.001) and dose related increases in the relative weightsof liver, stomach, spleen, testis, lungs and heart, at the 100 and 500 mg/kg of HU. Chronic HU treatment alsoproduced significant (p<0.05, p<0.001) dose related reductions in the serum levels of fasting blood glucose,bicarbonate, urea and creatinine while causing non-significant (p>0.05) alterations in the serum levels of sodium,potassium, alaninine transaminase, aspartate transaminase, alkaline phosphatase, total and conjugated bilirubin,total protein and albumin. Also, chronic oral treatment with HU produced significant (p<0.05, p<0.01, p<0.001)and dose-related increases in the red cell count, packed cell volume, haemoglobin concentration, platelet count,total leucocyte count and lymphocyte differential while producing significant (p<0.05) reductions in neutrophiland granulocyte differentials. HU also produced histological features of proliferations of the stomach epithelia,lung tissues, splenic white and red pulps, and testicular spermatogenic series. Following 14 days of oral toxicityreversibility test, there was no significant (p>0.05) reversal in the serum levels of the biochemical andhaematological parameters investigated, including the HU-induced histological lesions.Overall, results of this study showed that HU has a relatively low oral toxicity profile but its prolongeduse, particularly, at high doses should be with great caution.